12-week Brisk Walking Improved Chronotropic Response in Hypertensive Patients - Wu, Tong; Yan, Yan; Luo, Yong; Wang, Zhengzhen; Wang, Yan (International Journal of Sports Medicine, 2023)
We investigated the effects of 12-week brisk walking on chronotropic response in hypertensive patients aged 40–69. 77 participants in exercise group underwent 12-week brisk walking, while 66 participants in control group received health education. Chronotropic parameters, resting blood pressure, and physical fitness including peak oxygen consumption (VO2peak) were measured. After 12 weeks, the systolic blood pressure (SBP) was decreased (−6.104 mmHg, 95%CI −8.913 to −3.295 mmHg, P<0.0001), while metabolic chronotropic relationship (MCR) slope and VO2peak were increased (0.073, 95%CI 0.001 to 0.145, P=0.046; 1.756 mL/kg/min, 95%CI 0.891 to 2.622 mL/kg/min, P<0.0001) in exercise group compared to baseline. The chronotropic response index (CRI) at 25–75 W load were decreased (−0.210, 95%CI −0.307 to −0.112, P<0.0001; −0.144, 95%CI − 0.204 to −0.083, P<0.0001; −0.078, 95%CI −0.135 to −0.022, P=0.007) in control group after 12 weeks. The relative changes (%Δ) of systolic and diastolic blood pressure were negatively correlated with %ΔVO2peak (r=−0.233, r=−0.187), while %ΔMCR and %ΔCRI at 50–75 W load were positively correlated with %ΔVO2peak after 12 weeks (r=0.330, r=0.282, r =0.370). %ΔSBP was also positively correlated with %ΔMCR (r =−0.213). In conclusion, 12-week brisk walking reduced SBP by improving chronotropic response in hypertensive patients aged 40–69. The enhanced chronotropic response was associated with enhanced cardiorespiratory fitness.
Keywords: hypertension; chronotropic response; aerobic exercise; brisk walking